Analisis Penerapan Manajemen Risiko Berbasis ISO 31000 pada Operasional Event Organizer: Studi Kasus Auliacorp Bandung - Andyka Maulana Prayoga; Indy Fauziah Hanifa; Putri Dewi Renggani; Dwi Julyansyah; Alfiana (Indo Publishing, 2025)
This research aims to analyze the implementation of the ISO 31000 risk management framework in the operations of a local Event Organizer (EO), case study Auliacorp Bandung, to address a research gap in Indonesia's small and medium-sized event service sector. The EO sector faces high risk exposure but often neglects formal frameworks. Using a qualitative descriptive approach, data was collected through interviews, observation, and documentation. Risk analysis was performed using a 5x5 matrix (Likelihood × Impact) which classified 35 risk events into Low (1-6), Medium (7-14), and High (15-25) categories. The evaluation results show that most risks (19 risks) are at a Medium level, but management must focus attention on eight High-category risks. The most critical risks are dominated by Financial issues (R16: Client payment failure, score 20) and Human Resources (R11 & R13: Crew fatigue and personnel shortage, score 15-16), followed by Operational risks (R02: Rundown error, score 16). The recommended risk treatments focus on strengthening contract clauses, payment verification, refining technical SOPs, and developing a freelance crew backup system. The study concludes that the implementation of the ISO 31000 framework is highly relevant and urgent for Auliacorp to ensure operational sustainability, minimize financial losses, and maintain the company's reputation.